SUN-LB61 Differential and Opposite Regulation of Acid Labile Subunit (ALS) Versus Insulin-Like Growth Factor I (IGF-I) by Oral Estrogens in Premenopausal Women - Schilbach, Katharina (J Endocr Soc, 2020)
Background: The impact of estrogens (E2) on the growth hormone (GH)/IGF-I axis is known to depend on route of administration: While oral E2 increases GH and decreases IGF-I, transdermal E2 has only limited or no effect. However, data concerning the impact of E2 on IGF binding protein 3 (IGFBP 3) and ALS are less clear. One study in girls demonstrated higher ALS with oral E2, while the opposite was suggested for postmenopausal women. No data are available for healthy premenopausal women.Methods: We measured IGF-I, IGFBP 3 and ALS in fasted healthy adults (93 males (M), 35 premenopausal women without E2-containing oral contraception (FPRE), 37 premenopausal women with E2-containing oral contraception (FPREOC) and 34 postmenopausal women (FPOST)). IGF-I and IGFBP 3 were measured using the IDS-iSYS chemiluminescence immunoassay, and ALS by an in-house immunofluorometric assay (limit of quantification (LoQ) < 50 mU/ml, range 50 - 4000 mU/mL).Results: Median age (range) was 33 (20 - 76), 28 (20 - 44), 24 (21 - 36) and 56 (49 - 70) years for M, FPRE, FPREOC and FPOST, respectively. As expected, IGF-I was lower in FPREOC compared to FPRE (median IGF-I xULN (IQR) 0.56 (0.45 - 0.73) and 0.72 (0.63 – 0.80), P = 0.0017, Kruskal-Wallis). ALS was significantly higher in FPREOC compared to all other groups (mean ALS in M, FPRE, FPREOC and FPOST: 636, 708, 861 and 648 mU/mL, respectively, ANOVA P < 0.0001, Dunnett’s post-hoc test: M vs FPREOC: P < 0.0001, FPRE vs FPREOC: P = 0.0007, FPOST vs FPREOC: P < 0.0001). IGFBP 3 was not different in females with and without oral E2 (median IGFBP 3 xULN (IQR) FPREOC vs FPRE: 0.62 (0.54 - 0.67) vs 0.60 (0.49 – 0.76), Kruskal-Wallis P = 0.295, Dunn’s post-hoc test: P > 0.9999). This was also true between all other groups (Dunn’s post-hoc test: P ≥ 0.4). In our adult cohort, ALS exhibited negative correlation with age (Pearson r = -0.282, P = 0.0003), similar to IGF-I and IGFBP 3. While IGF-I exhibited a moderate negative correlation to BMI (Pearson r = -0.25, P = 0.0013), IGFBP 3 and ALS were not significantly related to BMI.Conclusion: While IGF-I, IGFBP 3 and ALS all are known to be secreted in response to GH, and IGF-I and ALS are assumed to be produced by the same cells in the liver (hepatocytes), the three GH dependent biomarkers appear to be differently regulated by metabolic factors and oral E2. Only IGF-I has some modest association with BMI. Oral E2 is associated with reduced IGF-I, unchanged IGFBP 3 but increased ALS. While the mechanism behind the differential regulation remains to be uncovered, E2 therapy must be taken into account when interpreting IGF-I and ALS concentrations.